THE CORRELATION OF FAMILY SUPPORT AND HEALTH WORKER SUPPORT WITH MEDICATION ADHERENCE OF TB PATIENTS AT PUSKESMAS (PUBLIC HEALTH SERVICE) TAMAN - Yuliani Puji Lestari; Tintin Sukartini; Makhfudli Makhfudli (Critical Medical and Surgical Nursing Journal (CMSNJ), 2020)
Introduction: Tuberculosis (TB) is a world health problem. This study aims to determine the relationship between family support and health worker support with adherence to taking medication for TB patients at Puskesmas Taman.Method: The research design used was a cross sectional study. The number of samples of 50 respondents used purposive sampling technique. The independent variables were family support, health worker support. The dependent variable was medication adherence. Data were collected using a questionnaire and analyzed using the Spearman rho test with a significance level of α <0.05.Result: It was found that there was a relationship between family support (p = 0.001) and support from health workers (p = 0.001) with adherence to taking medication in TB patients at TB health centers.Conclusion: Adherence to taking medication is related to family support and support from health workers. In providing interventions regarding adherence to taking medication for TB patients, it is expected that they can pay attention to the functions of the family and health workers so that the intervention can run optimally and the prevalence of TB decreases.